The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1177/0361684315577383
|View full text |Cite
|
Sign up to set email alerts
|

Gender Biases in (Inter) Action

Abstract: Although explicit stereotypes of women in the workplace have become increasingly positive (Duehr & Bono, 2006), negative stereotypes persist at an implicit level, with women being more likely associated with incompetent-and men with competent-managerial traits (Latu et al., 2011). Drawing upon work on self-fulfilling prophecies and interracial interactions, we investigated whether and how implicit and explicit gender stereotypes held by both male interviewers and female applicants predicted women's interview o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 51 publications
(99 reference statements)
2
15
1
Order By: Relevance
“…For example, when investigating the effects of White physicians' racial bias on Black patients, Penner and colleagues (Penner et al 2010) found that Black patients reacted most negatively when they interacted with a White physician who was high in implicit but low in explicit bias (aversive racist). Similarly, within mixed-gender job interviews, Latu and colleagues (Latu et al 2015) showed that male interviewers' explicit and implicit stereotypes interacted to predict lower performance of women applicants. Female job candidates' performance (as rated by trained external evaluators) suffered the most when they were interviewed by male interviewers who were, at the same time, high in implicit but low in explicit gender stereotypes (aversive sexist).…”
Section: Gender Stereotypes In Face-to-face Negotiationsmentioning
confidence: 95%
See 4 more Smart Citations
“…For example, when investigating the effects of White physicians' racial bias on Black patients, Penner and colleagues (Penner et al 2010) found that Black patients reacted most negatively when they interacted with a White physician who was high in implicit but low in explicit bias (aversive racist). Similarly, within mixed-gender job interviews, Latu and colleagues (Latu et al 2015) showed that male interviewers' explicit and implicit stereotypes interacted to predict lower performance of women applicants. Female job candidates' performance (as rated by trained external evaluators) suffered the most when they were interviewed by male interviewers who were, at the same time, high in implicit but low in explicit gender stereotypes (aversive sexist).…”
Section: Gender Stereotypes In Face-to-face Negotiationsmentioning
confidence: 95%
“…In the current study we wish to expand this prior research by investigating the interactive roles of implicit and explicit gender stereotypes on face-to-face negotiations, while concomitantly investigating, for the first time to our knowledge, the influence of additional contextual factors such as gender and power roles. Drawing from the racial bias literature (Penner et al 2010) as well as job interview research (Latu et al 2015), we suggest that negotiating counterparts' implicit and explicit stereotypes will act in conjunction to predict women's ability to claim value at the bargaining table. More specifically, we reason that women's negotiated outcomes may be a function of their negotiation counterparts' explicit and implicit gender stereotypes, and we expect women's performance to suffer the most when they negotiate with men who are simultaneously high in implicit, but low in explicit, stereotypes (i.e., aversive sexists).…”
Section: Gender Stereotypes In Face-to-face Negotiationsmentioning
confidence: 98%
See 3 more Smart Citations